Pengenalan Potensi UMKM Gula Merah dengan Kemasan Gula Semut dan Gula Batu di Desa Barambang, Kec. Sinjai Borong, Kab. Sinjai Melalui Video Dokumenter - Rahmatullah Rahmatullah; Sartika Sartika; Rifkah Damayanti Abduh; Andi Elfira Yusria; Dielci Maryam Virginia; Fajar Abdillah; Resky Aulia M; Muhammad Dzakwan Zhafran; Muhammad Alisofyan Ar Djambia; Kasma N; Umar Sabirin (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The implementation of KKN is contained in the third point of the Tri Dharma of higher education. This is intended so that students can gain knowledge that is not available on campus. Apart from that, students also carry out community empowerment and service in their work areas from the knowledge they have gained on campus. The aim of this "MSME Palm Sugar Documentary Video" is to help palm sugar craftsmen promote their products using documentary videos which are made and then posted on social media so they can be seen by the public. Apart from that, this palm sugar product can also be known to many people through documentary videos that have been made, so that not only the local village community knows about this palm sugar product but also the entire Indonesian people. The work program "Video Documentary of Palm Sugar UMKM" is very influential in improving the creative economy of palm sugar UMKM to expand the marketing of their products. To be recognized by the general public.